Profil Disolusi Tablet Amlodipin dan Perbandingan Kadar Dua Produk Generik dengan Produk Inovator - Alegantina, Sukmayati; Isnawati, Ani (Jurnal Kefarmasian Indonesia, 2015)
Amlodipine is an antihypertensive and antianginal drug belonging to the class of dihydropyridine calcium antagonist (calcium ion antagonist). Amlodipine patent term expired in 2007, thus nowadays some national pharmaceutical manufacturers produce amlodipine as generics and branded generics medicine. In order to determine the quality of generic amlodipine, dissolution profile and contents of two generic amlodipine were studied by comparing them with their innovator product. The dissolution test was carried out using a type 2 (paddle) and the dissolved content was determined by using UV spectrophotometer, whereas amlodipine content tablet was determined by using HPLC (High Performance Liquid Chromatography). The results showed that all of the three tablets met the FDA requirements of dissolution, i.e.within 30 minutes they should be dissolved not less than 85%. All of the three tablets had the same dissolution profile p=0,521 (CI=95%), whereas both the generic and branded generic tablet compared to the innovator product had similar or comparables profile , (f2>50). The content of all three tablets are not significantly different with p=0,08 (CI = 95%). The highest content of amlodipine was found in amlodipine a tablet with an average content of 102,69%.